OUTCOMES-BASED ASSESSMENT: NECESSARY EVIL OR TRANSFORMATIVE POTENTIAL - Bozalek, Vivienne (Social Work/Maatskaplike Werk, 2009)
Social work educational providers at higher educational institutions (HEIs) in South Africa have been obliged since 2008 to engage with the South African Qualifications Authority’s (SAQA’s) qualification of the Bachelor of Social Work (BSW), which was registered in June 2003 in the National Qualifications Framework (NQF). In February 2004 the South African Social Service Professions Council (SACSSP) wrote a letter to all social work educational providers requesting them to benchmark their current curriculum against the new minimum standard requirements of the BSW on a template. Furthermore, providers of social work education and training had to indicate how they would change their current learning programmes to accommodate the minimum standards, which encompass 27 exit-level outcomes and their associated assessment criteria. Providers had until June 2006 to comply with the requirements of the new BSW qualification and had to start implementation of the learning programme in January 2007.